2021
DOI: 10.1021/acscatal.0c04186
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of the First Two Glycerol Dehydrogenation Steps Determined Using Scaling Relationships

Abstract: Glycerol is a byproduct of biodiesel production and an abundant feedstock that can be used for the synthesis of highvalue chemicals. There are many approaches for glycerol valorization, but, due to the complicated reaction mechanism, controlling which products are produced is challenging. Here, we describe glycerol's chemical selectivity for different metallic catalysts using descriptors for carbon (mainly *C, *CH 2 OH) and oxygen (mainly *O, CH 3 O*). The quality of these descriptors and the weighted combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 60 publications
2
32
0
Order By: Relevance
“…These measurements agree with assumptions made in kinetic studies that sought to explain differences in apparent E a for hydrogenolysis of alkanes under conditions that H* was the MARI and transition states formed only after the desorption of several H*-atoms, consistent with results from DFT calculations. , Our group reported that activation barriers for alkene epoxidation on various metal-incorporated BEA (M-BEA) catalysts correlate linearly with adsorption enthalpies of the corresponding epoxide measured by isothermal titration calorimetry . We anticipate that appropriate microcalorimetry experiments (e.g., enthalpies of dissociative adsorption of small alcohols or aldehydes) would be useful in the development of accurate scaling relationships, as shown computationally by Valter et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These measurements agree with assumptions made in kinetic studies that sought to explain differences in apparent E a for hydrogenolysis of alkanes under conditions that H* was the MARI and transition states formed only after the desorption of several H*-atoms, consistent with results from DFT calculations. , Our group reported that activation barriers for alkene epoxidation on various metal-incorporated BEA (M-BEA) catalysts correlate linearly with adsorption enthalpies of the corresponding epoxide measured by isothermal titration calorimetry . We anticipate that appropriate microcalorimetry experiments (e.g., enthalpies of dissociative adsorption of small alcohols or aldehydes) would be useful in the development of accurate scaling relationships, as shown computationally by Valter et al…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that binding energies of CH 3 O* or CH 2 OH* intermediates obtained from DFT calculations describe rates for the dehydrogenation of glycerol on metals’ surfaces (Ru, Co, Rh, Ir, Ni, Pd, Pt, Cu, etc.) better than BE M‑O or BE M‑C . These comparisons indicate that the binding mode of the molecular fragments (i.e., μ 3 -C atoms compared to η 1 (C)–CH 2 OH*) and interactions between moieties of the adsorbed species (e.g., hydroxyl groups) and the surface significantly influence the stability of these complexes and much be considered for accurate predictions.…”
Section: Hydrogenolysis Of Biomass-derived Oxygenatesmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, oxidation of DHA leads to the formation of HPA, while GLAD can be oxidized to GLA and then to GA and FA by breaking the C–C bond. At this stage, it is not clear why the secondary hydroxyl group is the preferred oxidation site, and a full understanding of the oxidation pathway may require a thorough theoretical inspection, which is still under-developed due to the complicated oxidation intermediary steps and a large number of possible products, even on noble metal catalysts …”
Section: Resultsmentioning
confidence: 99%
“…At this stage, it is not clear why the secondary hydroxyl group is the preferred oxidation site, and a full understanding of the oxidation pathway may require a thorough theoretical inspection, which is still under-developed due to the complicated oxidation intermediary steps and a large number of possible products, even on noble metal catalysts. 47 Nevertheless, our work opens a new door toward selective electrochemical oxidation of glycerol to value-added chemicals using noble metal-free electrocatalysts, with a large library of potential electrocatalysts being developed for water oxidation reactions to choose from. 48−50 Our preliminary results show that similar EGOR activity and enhancement were also achieved on the electrodeposited Ni−B i /CF electrode.…”
Section: And B(oh)mentioning
confidence: 99%